Democracy and dictatorship in Europe : from the Ancien régime to the present day - Berman, Sheri (New York Oxford University Press, 2019)
"In Democracy and Dictatorship in Europe, Sheri Berman traces the long history of democracy in its cradle, Europe. She explains that in fact, just about every democratic wave in Europe initially failed, either collapsing in upon itself or succumbing to the forces of reaction. Yet even when democratic waves failed, there were always some achievements that lasted. Even the most virulently reactionary regimes could not suppress every element of democratic progress. Panoramic in scope, Berman takes readers through two centuries of turmoil: revolution, fascism, civil war, and--finally--the emergence of liberal democratic Europe in the postwar era. A magisterial retelling of modern European political history, Democracy and Dictatorship in Europe not explains how democracy actually develops, but how we should interpret the current wave of illiberalism sweeping Europe and the rest of the world"--
Includes bibliographical references (pages [409]-516) and index.
Keywords: Democracy -- Europe -- History; Dictatorship -- Europe -- History; Europe -- Politics and government